The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1103/physrevd.84.043532
|View full text |Cite
|
Sign up to set email alerts
|

Mass-radius relation of Newtonian self-gravitating Bose-Einstein condensates with short-range interactions. II. Numerical results

Abstract: We develop the suggestion that dark matter could be a Bose-Einstein condensate. We determine the mass-radius relation of a Newtonian self-gravitating Bose-Einstein condensate with short-range interactions described by the Gross-Pitaevskii-Poisson system. We numerically solve the equation of hydrostatic equilibrium describing the balance between the gravitational attraction and the pressure due to quantum effects (Heisenberg's uncertainty principle) and short-range interactions (scattering). We connect the noni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
377
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(404 citation statements)
references
References 64 publications
23
377
3
1
Order By: Relevance
“…There are stable Bose star configurations of axions, which are supported by pressure [49][50][51][52], and it has been suggested that these could be produced by further contraction of miniclusters [10,11]. If they do exist, axion stars lead to distinctive observational signatures for example through gravitational lensing [53], or even gravitational wave emission in collisions [54].…”
Section: Axion Starsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are stable Bose star configurations of axions, which are supported by pressure [49][50][51][52], and it has been suggested that these could be produced by further contraction of miniclusters [10,11]. If they do exist, axion stars lead to distinctive observational signatures for example through gravitational lensing [53], or even gravitational wave emission in collisions [54].…”
Section: Axion Starsmentioning
confidence: 99%
“…A repulsive quartic would improve star stability, but could make the dynamics of star formation even harder to realise. The stability bound on an axion Bose star is well known [49,50] 1) and above this the star is expected to either fragment into smaller objects or collapse to a black hole. If the miniclusters are produced by PQ symmetry breaking the possible star masses are very strongly constrained.…”
Section: Axion Starsmentioning
confidence: 99%
“…Concerning the dark matter problem, non-thermal candidates like the axion [13][14][15][16][17][18][19][20][21] or other massive scalar [22][23][24][25] or pseudoscalar fields [26][27][28][29][30][31][32] also fall in this class. These models can be interpreted as Bose-Einstein condensates, where the scalar particles occupy the lowest quantum state of the potential [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Finally, the possibility of ultra-light scalar fields as dark matter candidates has been explored in different works [49][50][51][52][53][54][55][56][57][58] by tuning appropriately the potential and initial conditions [54]…”
Section: Introductionmentioning
confidence: 99%
“…The galactic masses in the framework of the condensate model were discussed in [32,33], and the effects of the finite temperature of the condensate on the density profiles were studied in [34]. The equilibrium properties of Newtonian self-gravitating Bose-Einstein condensates with short-range interactions were investigated in detail in [35,36]. The study of the cosmological implications of the Bose-Einstein condensation has also become an active field of research [37][38][39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%